Respon Pemberian Pupuk Kompos dan NPK Terhadap Produksi Tanaman Kangkung Darat - Daniel, MHD Yandri; Harahap, Lutfi Henderlan (UNIVERSITAS LABUHANBATU, 2024)
This research aims to determine the effect of fertilizer dosage on the growth of land kale (Ipomoea reptansPoir). The research was carried out using a completely randomized experimental design (DEC) involving several fertilizer dose treatments, namely 0 kg/ha, 50 kg/ha, 100 kg/ha, and 150 kg/ha. Each treatment was repeated three times to ensure the accuracy of the results. The parameters observed included plant height, number of leaves, and land kale plant biomass. The results showed that fertilizer dosage had a significant effect on plant growth. A fertilizer dose of 100 kg/ha gave the best results on all growth parameters, followed by a dose of 50 kg/ha and 150 kg/ha. A fertilizer dose of 0 kg/ha shows the lowest growth. These findings indicate that optimal fertilization is very important to increase the growth yield of land kale. This research provides recommendations for efficient fertilizer doses to support maximum growth of land kale plants. Keywords: fertilizer, land kale, fertilizer doses